Virtual Werribee: A planning support tool - Abdul Ghani, M.; Datta, Sambit; Beynon, D. (Modelling and Simulation Society of Australia and New Zealand, 2011)
Virtual Werribee is collaborative research in applying 3-D modelling and visualisation as a planning support tool in comparison to 2-D plans and drawings. It was a joint initiative involving Deakin University and Wyndham City Council to demonstrate the use of 3-D visualisation for planning process in the actual context of a planning authority in Australia. The objective of this project was to assist the council in preparing for the revised Local Structure Plan. By reconstructing the council's data into easily understood information, 3-D model and visualisation served as a verification and discussion tool for decision making. The integration of wider site context also provided a better understanding of the surrounding development areas. This could equip other stakeholders as well as the community to participate in council's planning agenda activities, such as increasing the urban density and building heights limit. Virtual Werribee included the development planning agenda, categorised as new, re-development and hypothetical. The modelling process progressed with sufficient date from the council. Some changes to the initial plan were made, including the use of CAD modelling software instead of GIS software, and production of a block model with selected detail buildings, instead of a full draped 3-D model. The council decided that the block model would be sufficient for their planning purposes. This was determined while taking into consideration the available facilities at the council.The potentials of the model as a planned tool were demonstrated in this paper, and further compared to the council's existing materials prepared by the project developers. The advantages of the 3-D interactive model and visualisation over the conventional materials have provided the council officer with a tool for better empowerment in the planning process. This was also evident in the increasing engagement level between the officer and the model as the process developed. As a result of this, the project scope has also expanded, finally covering the entire city. While Virtual Werribee has the potential to better communicate council's planning agendas to the stakeholders and the community, the key factor, coupled with its visualisation components, was its interactive capability. Property layers with aerial site image that provided a realistic background served as a virtual city platform for different users. Although limited in its analytic capability found in GIS software, this model offered high visualisation content to assist visual impact assessment through its interactive mode along with a series of still images and a simulation movie.